Pelaksanaan standar proses pembelajaran interaktif inspiratif dan menyenangkan pada mata pelajaran sejarah kebudayaan Islam - Putri, Elvira Rismaya; Fitria, Aulia; Koto, Ghefira Sakina; Alifiandra, Hilman; Permana, Hinggil (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2025)
This study aims to describe the implementation of interactive, inspiring, and enjoyable learning process standards in the Islamic Cultural History (IS) subject at MTsN 5 Karawang. The main focus of this study is how teachers apply the principles of interactive, inspiring, and enjoyable learning in IS learning activities. The study used a descriptive qualitative approach with an IS teacher with more than seven years of experience as the subject. Data were collected through semi-structured interviews, observation, and documentation, then analyzed using the Miles & Huberman model through data reduction, data presentation, and drawing conclusions. The results showed that teachers had attempted to create interactive learning through the use of teaching modules, two-way discussions, the use of media such as PowerPoint and infocus, and strengthening understanding through mind mapping and projects. These findings emphasize the importance of the role and innovation of teachers in improving the quality of learning.